Effects of dietary fermented mealworm larvae and stocking density on performance, blood stress indicator and intestine parameters of broilers - Sarica, Ş; Yavuz, M; Sanli, ER; Kati, A; Altuntas, S; Alatas, MS; Ekici, M; Yazarel, S; Keskintas, AT (Journal of the Hellenic Veterinary Medical Society, 2024)
The present study was conducted to evaluate the effects of the supplementation of defatted mealworm larvae meal fermented with probiotics as a new antibacterial feed additive to the diet of broilers reared under normal- (NSD) and high- (HSD) stocking density on growth performance, blood and slaughtering parameters, microorganism content and morphology of ileum and short-chain fatty acids content of ceca. A total of four hundred and fifty one-d-old Ross 308 male broiler chicks were randomly distributed into six groups of similar mean weight, each containing five replicates. Experimental treatments consisted of a 2 x 3 factorial arrangement with two levels of stocking density (12 birds/m2 as NSD and 18 birds/m2 as HSD) and three different mash diets: CONT- a corn-soybean meal-based diet containing no fermented defatted mealworm larvae meal (FDM) (0%); FDMLP- the diet obtained by supplementing DM fermented with Lactobacillus plantarum to the CONT diet (0.4%); FDMLB- the diet obtained by supplementing DM fermented with Lactobacillus brevis to the CONT diet (0.4%). HSD significantly decreased the growth performance except feed conversion ratio (FCR), carcass yields (CYs), Lactobacillus spp. content and villus height (VH) and villus surface area (VSA) of ileum and short-chain fatty acids (SCFAs) concentrations of ceca, but, increased the blood heterophil/lymphocyte (H/L) ratio and Escherichia coli content and crypt depth (CD) of ileum of broilers compared to NSD. The FDMLP and FDMLB diets significantly improved the FCR and increased final body weight (BW), BW gain, Lactobacillus spp. content and VH and VSA of ileum and SCFAs concentrations of ceca, however, reduced the blood H/L ratio and Escherichia coli content and CD of ileum of broilers when compared to the CONT diet. In conclusion, FDMLP and FDMLB can be utilized as new antibacterial feed additives in broiler diets regardless of stocking density.